Upconversion Nanocomposite Materials With Designed Thermal Response for Optoelectronic Devices - Martínez, Eduardo D.; Brites, Carlos D. S.; Carlos, Luís D.; Urbano, Ricardo R.; Rettori, Carlos (Frontiers in Chemistry, 2019)
Upconversion is a non-linear optical phenomenon by which low energy photons stimulate the emission of higher energy photons ones. Applications of upconversion materials are wide and cover diverse areas such as bio-imaging, solar cells, optical thermometry, displays, and anti-counterfeiting technologies, among others. When these materials are synthesized in the form of nanoparticles, the effect of temperature on the optical emissions depends critically on their size, opening new opportunities for innovation. However, it remains a challenge to achieve upconversion materials that can be easily processed for their direct application or for manufacture of optoelectronic devices. In this work, we developed nanocomposite materials based on upconversion nanoparticles (UCNPs) dispersed in a polymer matrix, either polylactic acid (PLA) or poly(methyl methacrylate) (PMMA). These materials can be processed from solution to form thin film multilayers, which can be patterned by applying soft-lithography techniques to produce desired features in the micro-scale, and luminescent tracks when used as nanocomposite inks. The high homogeneity of the films, the uniform distribution of the UCNPs and the easygoing deposition process are the distinctive features of such approach. Furthermore, the size-dependent thermal properties of UCNPs can be exploited by a proper formulation of the nanocomposites in order to develop materials with high thermal sensitivity and thermochromic response. Here we thus present different strategies for designing optical devices through patterning techniques, ink dispensing and multilayer stacking. By applying upconverting nanocomposites with unique thermal responses, local heating effects in designed nanostructures were observed.